ANALISIS HUBUNGAN FUNGSIONAL JUMLAH MASYARAKAT MUSLIM DAN PEMBANGUNAN MASJID/MUSHOLAH DI SULAWESI SELATAN - Mifda Hilmiyah; Khaerun Nisa; Jeni Ayu (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2018)
Today the Muslim community is vying to establish a mosque / musholah. Because now the mosque / musholah not only used as a place of worship for Muslims. But also as a place of deliberation, a place to improve the intelligence and knowledge of the Muslims and the development and development of cadres of the leaders of the ummah.The type of this research is quantitativeand research method are correlation and regression analysis.Correlation analysis is used to test the significance and the relation between variables of Muslim population and mosque building. Meanwhile, regression analysis aims to determine the significance of the influence of Muslim population on building mosques in South Sulawesi Province. The results of this research indicate that the functional relationship between the number of Muslim population and the number of mosque buildings in South Sulawesi Province in 2015 is a positive linear pattern, the higher the Muslim population the higher the number of mosque buildings. Based on the results of correlation analysis obtained correlation coefficient between variables is strong that is 0.894 and significantly correlated. Meanwhile, based on regression analysis, it is found that there is significant influence between population and mosque building in South Sulawesi Province in 2015.